If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -1) + 4 = 9 + 7x Reorder the terms: 8(-1 + x) + 4 = 9 + 7x (-1 * 8 + x * 8) + 4 = 9 + 7x (-8 + 8x) + 4 = 9 + 7x Reorder the terms: -8 + 4 + 8x = 9 + 7x Combine like terms: -8 + 4 = -4 -4 + 8x = 9 + 7x Solving -4 + 8x = 9 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -4 + 8x + -7x = 9 + 7x + -7x Combine like terms: 8x + -7x = 1x -4 + 1x = 9 + 7x + -7x Combine like terms: 7x + -7x = 0 -4 + 1x = 9 + 0 -4 + 1x = 9 Add '4' to each side of the equation. -4 + 4 + 1x = 9 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 9 + 4 1x = 9 + 4 Combine like terms: 9 + 4 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 8x=7y+9 | | 12x^2+16x-28=0 | | 5x+4=44 | | 7g+12=9g-6 | | 3(2x-2)=4x | | 6x-1=41 | | 3(h-4)+5=60 | | 13x+2x=-150 | | 5m+42=11m | | (4x)*2=16 | | 5(8x-4)=44x | | 2-(x+5)=4x-8 | | 3(x+8)=33 | | 6(6n+7)=7(6n+6)+5 | | 7x-x=36 | | 5w+10=0 | | 6x-5y=9 | | 16(x+2)=4(4x+1)+28 | | -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 |